Karakterisasi Genetik TRICHODERMA SPP Indigenus Rizosfir Pisang yang Berpotensi Pengendalian FUSARIUM OXYSPORUM F. SP. CUBENSE Penyebab Penyakit Layu Fusarium pada Pisang - Nurbailis, Nurbailis; Martinius, Martinius (Lembaga Penelitian Universitas Negeri Padang, 2008)
The objective of the research was to characterize the genetic variation of Trichoderma spp. Study of genetic characters used Random Amplified Polymorphic DNA-Polymerase Chain-reaction (RAPD-PCR) that amplicated with four primers (OPA 2, OPA 17, OPB- 05 and Primer 2).Â Analysis result of genetic variation of Trichoderma spp make as dendrogram. The result of the research indicated that : 1) Trichoderma spp. had the great genetic variation, 2)Trichoderma isolate from the same region did not always have the same genetic profile, 3) S6 and T1 isolates were effective to inhibit the growth of Fusarium oxysporum f. Sp. cubenseÂ than the others butÂ had a different genetic profile. Keywords : Trichoderma spp, Fusarium oxysporum f.sp.cubense, karakterisasi genetik